DUAL ROLE CONFLICT WITH BURNOUT SYNDROME IN NURSES (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Burnout syndrome in nurses who are too busy tall can influence ability individual in face environment work , so that arise various consequence Good both mentally and physically physical which can seriously disrupt the service process . Research This aiming For know connection conflict role double with burnout syndrome in nurses at RSNU Tuban . Research This is non- experimental research with design analytic correlational and the approach used is cross sectional . Respondents in study This totaling 40 respondents with use total sampling technique . Variables free is conflict role double and variable tied up is burnout syndrome. The instrument used is questionnaire . Research results show conflict role double burden and burnout syndrome in nurses at RSNU Tuban is in the category moderate . The statistical test used is the Spearman rho test with α = 0.05 and obtained value of ρ = ​​0.000 (ρ =